Characterization of the bacteriocins and the PrtR regulator in a plant-associated Pseudomonas strain - Fernandez, Maricruz (2020)
The emergence of antibiotic resistant bacterial strains demands the development of new antimicrobial agents. In the last decades, bacteriocins have gained significant interest due to their potential application as biopreservatives in the food industry and as therapeutic agents in medicine. Recent studies project the use of these antimicrobials in agriculture as biocontrol agents. The characterization of bacteriocins and their genetic regulation, however, have been scarcely studied in plant-associated bacteria. In this report, an in-silico and proteomic analysis was performed to identify the bacteriocins produced by Pseudomonas fluorescens SF4c. More than one functional bacteriocin was detected in this strain (S-type bacteriocins and phage-tail-like bacteriocins [tailocins]). It is known that the regulator PrtR represses bacteriocin production in P. aeruginosa under normal condition. However, the mechanism for tailocin regulation remains unknown in plant-associated pseudomonads. In this work, an orthologue of the prtR of P. aeruginosa was identified in the SF4c-tailocin cluster and a prtR null mutant constructed. The expression and production of tailocins was abolished in this mutant; thus evidencing that, unlike P. aeruginosa, PrtR is a positive regulator of tailocins expression in P. fluorescens.